Pengaruh Pelatihan Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi di PT. Nikomas Gemilang Bagian Personalia Divisi Nike) - Awaliah, Wulan; Siti Khoirotunnisa; Siti Adellia; Didit Haryadi (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
Job training and work environment play an important role in improving employee performance in every company, especially at PT. Nikomas Gemilang. In the Personnel Department of the Nike Division, not only in this company, even throughout the world it is said that every worker will be paid by the employer, so that performance will increase. Employees will run smoothly if their job training and work environment are adequate, however, most companies in Indonesia pay little attention to their workers, thus the level of employee performance in these companies decreases. This research aims to find out: 1) To find out the effect of job training on employee performance levels. 2) To determine the influence of the work environment on employee performance levels. 3) To determine the effect of job training and work environment on employee performance levels. This research uses primary data obtained from distributing questionnaires to all employees of PT. Nikomas Gemilang in the Personnel Department of the Nike Division. The population in this study was 14 respondents. Job Training, Work Environment, Employee Performance